Inovasi Pembelajaran di Perguruan Tinggi melalui Blended Learning untuk Meningkatkan Keterampilan Membaca Kritis Mahasiswa - Sakaria Sakaria; Asis Nojeng (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
Innovations in higher education learning systems that adapt to advances in digital technology are designed to encourage students to be more active in learning activities and to improve their critical thinking and problem-solving skills. Critical reading is a critical thinking skill that consists of mental processes such as analysis, synthesis, and evaluation. The blended learning model is an innovative approach to higher education that combines face-to-face learning with online learning. Through video conferencing and online discussion forums, students can interact with reading materials, share ideas, and clarify their understanding. This study aims to analyze the impact of implementing blended learning on improving students' critical reading skills in higher education. The results of the study indicate that the implementation of the blended learning model has an impact on improving students' critical reading skills. This is evidenced by the difference between the average initial and final critical reading skills of students. The blended learning model encourages students' independent engagement in learning outside the classroom, enabling them to be more active in analyzing, synthesizing, and evaluating reading texts.